MECHANISTIC ROLE OF VARUNA (CRATAEVA NURVALA) EXTRACT ON THYROID GLAND AND ITS HISTOLOGY THROUGH IODOTHYRONINE DEIODINASES - Kaur, Arshvir; Verma, Santosh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Crataeva nurvala (CN) is used for its therapeutic effects, but its effect on the thyroid gland in euthyroid conditions and mechanism behind its thyrotropic activity in hypothyroidism is still not explored. This study screened the pharmacological effect of the ethanolic extract of the bark of CN on thyroid hormones, free and total thyroxine (FT4 and T4), triiodothyronine (T3), thyroid-stimulating hormone (TSH) levels, and thyroid histology in normal Swiss albino female mice. Methods: Eighteen animals of 28â€“33 g were segregated into three groups: Group I treated with vehicle (NOR+VEH), Group II administered CN 400 mg/kg (NOR+CN 400), and Group III given CN 600 mg/kg (NOR+CN 600), for 15 days, per os (p.o.). The variation in the T4, FT4, T3, and TSH levels was recorded using ELISA, 24 h after the last dose, and T3/T4 ratio thus calculated along with the histopathological studies of the thyroid gland. Results: The findings were presented as mean Â± standard error of the mean, using one-way ANOVA, followed by Dunnett's post-tests to compare all columns with the control. NOR+CN 600 has shown thyroid protective effect through retaining euthyroid profile, normal T3/T4 ratio, and near-normal histology. However, NOR+CN 400 had shown the significant decline in T3/T4 ratio and pathological changes in thyroid histology, in comparison with the control and NOR+VEH group. Conclusion: The higher dose of CN was found to sustain the euthyroid levels through retention of iodothyronine deiodinases activity, facilitating the peripheral conversion of T4 to T3, and in retaining normal histoarchitecture of the thyroid gland in contrary to a lower dose.